Evaluation of the Cytomorphometric Changes Observed in the Oral Mucosal Cells Exposed to Computed Tomography - Srii, Ritesh (Journal of College of Medical Sciences-Nepal, 2018)
Background: Radiography forms an important as well as an integral part of diagnosis which is used in various fields of medical and dental services to give an appropriate diagnosis. But, diagnostic radiations also induce some amount of damage to the cell at cytogenetic levels, depending on the dosage of the radiation administered. Objective: The objective of the present study was to observe the cytomorphometric changes in the buccal mucosa of patients who were exposed to computed tomography. Materials and methods: Study sample consisted of 15 patients who were exposed to Computed Tomography prior to treatment planning for placement of dental implants. Buccal mucosal smears were obtained pre and 10 days post radiation exposure by using a wooden tongue depressor and the contents were smeared on to clean glass slides and fixed using Biofix spray. Post fixation, these smears were stained using rapid PAP stain and viewed under compound microscope. Cytomorphometric analysis was performed using image ‘J’ software for 50 cells. Statistical analysis was done using SPSS software. Results: Cytomorphometric analysis of the buccal mucosal cells, did show variations in the nuclear and cellular parameters, but statistical significant results were obtained in case of nuclear diameter and nuclear area only suggesting genotoxic alterations following exposure to computed tomography. Conclusion: Oral buccal mucosal cells showed significant cytomorphometric changes in the nuclear parameters after exposure to X-rays during Computed Tomography. A longitudinal study consisting of a bigger sample size is required to evaluate the long-term effects of radiation on these buccal mucosa cells. Keywords: buccal mucosa; computed tomography; cytomorphometry; radiation.